Evaluating a grant development public involvement funding scheme: a qualitative document analysis - Foster, Alexis; Caunt, Sharon; Schofield, Holly; Glerum–Brooks, Karen; Begum, Samina; Gleeson, Phil; Prestwich, Graham; Baird, Wendy (Research involvement and engagement, 2024)
Background Undertaking Patient and Public Involvement (PPI) when developing health and social care research grant applications is critical. However, researchers may not have any funding to undertake PPI when developing grants. In response, the National Institute for Health and Care Research- Research Design Service for Yorkshire and the Humber in the United Kingdom, provided Public Involvement Fund Awards of up to £600 to fund PPI activity when researchers were developing grant applications. Researchers provided post-activity reports about how they utilised the Public Involvement Fund. These reports were analysed with the aim of evaluating the usefulness of the Public Involvement Fund and to provide learning about supporting researchers to undertake PPI when developing grants. Methods The project was a qualitative document analysis of 55 reports. Initially a researcher coded four reports and three Public Contributors provided feedback. Researchers coded the remaining reports and identified key findings. A workshop was held with the three Public Contributors to develop the findings. Results Researchers accessing the Public Involvement Fund award were generally early career researchers or clinicians who did not have other sources of funding for pre-grant PPI input. Researchers felt the award was useful in enabling them to conduct PPI, which strengthened their grant applications. Some researchers found that the award limit of £600 and guidance encouraging expenditure within three months, made it difficult to undertake PPI throughout the full grant development process. Instead, the majority of researchers consulted Public Contributors on one or two occasions. Researchers struggled to recruit diverse members or run group sessions due to the time pressures of grant deadlines. Researchers wanted training on undertaking PPI alongside the financial support. Conclusions Researchers, especially early career researchers found having a Public Involvement Fund award instrumental in enabling them to undertake PPI when developing grant applications. It would be beneficial for similar schemes to be widely available. Schemes need to provide sufficient funding to enable meaningful PPI and allow researchers to hold the award for long enough to facilitate involvement during the whole grant development process. Researchers continue to need training on undertaking PPI. Plain English summary Undertaking Patient and Public Involvement (PPI) when developing health and social care research grant applications is important. This ensures that patients have a voice in deciding what topics are researched. However, researchers often do not have funding to undertake PPI when developing grants. In response, a regional research advice service in the United Kingdom established a small grant scheme (up to £600) to fund PPI activity. This was called the Public Involvement Fund (PIF). Researchers developing health and social care grant applications could apply. After spending the funding, researchers wrote reports to explain how they used the Public Involvement Fund and the challenges they faced. We analysed 55 reports submitted over a three-year period to understand researchers’ experiences of the fund. Researchers found the funding critical in enabling them to undertake PPI. Many felt their grants were improved from consulting Public Contributors. For example, helping them to decide a topic, changing their research method or choosing a questionnaire. However, researchers sometimes struggled to recruit Public Contributors, particularly when the research was not about a specific health condition. Researchers wanted to be able to have the award for long enough to enable them to involve Public Contributors throughout the whole grant development process. Alongside funding, researchers also need specific training about undertaking PPI when developing grants. For example, how to recruit representative Public Contributors quickly. It is recommended that similar schemes to the PIF are available to enable researchers to fund PPI activities when developing grant applications.